2008
DOI: 10.1016/j.jclinane.2008.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent relationship between bispectral index and sedation level

Abstract: Interventions: The patients were allocated into 2 groups, group M (middle aged, <65 years) and group H (elderly, >65 years). Midazolam was administered at a bolus dose of 0.1 mg・kg -1 , followed by a continuous dose of 0.04 mg・kg -1 ・hr -1 , which was adjusted every 2 hrs to achieve a target level of sedation at 3-6 on Ramsay sedation scale (RSS), and buprenorphine was administered at a constant rate (0.625 μg・kg -1 ・hr -1 ).Measurements: BIS value, RSS, the dose of midazolam, body temperature, heart rate, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 16 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…The application of BIS in a study of monitoring the depth of anesthesia has attracted great attention [ 21 ]. Studies show that BIS can reflect the sedation of a variety of anesthetic drugs [ 22 ]. BIS can well reflect the depth of sedation of anesthetic drugs and is an accurate and sensitive index to evaluate the effect of anesthesia [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The application of BIS in a study of monitoring the depth of anesthesia has attracted great attention [ 21 ]. Studies show that BIS can reflect the sedation of a variety of anesthetic drugs [ 22 ]. BIS can well reflect the depth of sedation of anesthetic drugs and is an accurate and sensitive index to evaluate the effect of anesthesia [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that BIS is not a sensitive tool for measuring sedation induced with spinal anesthesia [ 18 ]. Furthermore, it has age-dependent differences, [ 32 , 33 ]. Accordingly, we used BIS as an adjunctive for clinical reference to the OAA/S scale.…”
Section: Discussionmentioning
confidence: 99%
“…In one pivotal study [183], fully awake subjects were shown to achieve BIS scores below 50 (i.e., corresponding with BIS during general anesthesia) when dosed with NMB drugs alone. Furthermore, additional research has suggested that BIS values should be interpreted with caution when patients are children [184], elderly [185], have known neurological disorders, or are taking psychoactive medications [186]. Beyond BIS, it has been noted that, "the use of DoA monitors remains a major controversy in anesthesiology.…”
Section: A Monitoringmentioning
confidence: 99%